A Rule‐Based Algorithm for Common Pilot Channel and Antenna Tilt Optimization in UMTS FDD Networks - Gerdenitsch, Alexander; Jakl, Stefan; Chong, Yee Yang; Toeltsch, Martin (ETRI journal, 2004)
In this paper we address the problem of capacity optimization in a Universal Mobile Telecommunication System (UMTS) radio network. We present an optimization algorithm for finding the best settings of the antenna tilt and common pilot channel power of the base stations. This algorithm is a parametric method, based on a set of rules. We evaluated our optimization technique on a virtual network scenario with 75 cells. For this scenario we show an increase in capacity compared to the initial settings of about 60 percent.